2021
DOI: 10.3390/su132413896
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Phytochemicals from Agricultural Wastes and Weeds on Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae)

Abstract: Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) is a polyphagous insect pest native to America. Due to its capacity for adaptation and migration, it is currently located in Africa, Asia, and Oceania, where it threatens agricultural crops. The ability of S. frugiperda to develop resistance to insecticides is one of the reasons for the continuous search for more effective, low-cost, and environmentally friendly control products. In the present work, the insecticidal activity of ethanolic and hexane ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…The tested concentrations significantly prolonged the duration of larvae after treated by (LPEO) and (LPEO-NPs) when compared to the control. These results agreed with the previously reported results obtained by 31 who reported that the dehydrated f Piper auritum 's ethanolic extract affected the survival of Spodoptera frugiperda by extending the larval and pupal stages and shortening the duration of the adult stage, with the strength of the effect depending on the extract's concentration. A slight significance in larval duration elongation treated with LC 15 and LC 50 of Lemongrass essential oil compared with control was reported by 32 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The tested concentrations significantly prolonged the duration of larvae after treated by (LPEO) and (LPEO-NPs) when compared to the control. These results agreed with the previously reported results obtained by 31 who reported that the dehydrated f Piper auritum 's ethanolic extract affected the survival of Spodoptera frugiperda by extending the larval and pupal stages and shortening the duration of the adult stage, with the strength of the effect depending on the extract's concentration. A slight significance in larval duration elongation treated with LC 15 and LC 50 of Lemongrass essential oil compared with control was reported by 32 .…”
Section: Discussionsupporting
confidence: 93%
“…Despite all surviving larvae in high concentrations pupated, the percentage of pupal mortality was lower than in the lower concentrations. In agreement with work reported by 31 , the pupal mortality of Spodoptera frugiperda was higher in all treatments of the larvae exposed to the LC 35 of ethanolic extract of Piper auritum than LC 50 and LC 56 . Additionally, nano-formulation using PEG of citrus peel essential oil extracted from different species including orange peel and lemon exhibited lethal activity against tomato T. absoluta have been reported by 21 .…”
Section: Discussionsupporting
confidence: 92%
“…The sample was further centrifuged for 15 min at 4000 rpm. After centrifugation, the lower layer of chloroform was taken and filtered with a 0.2 μm microfilter and injected into GC-MS [ 32 ]. The GC-MS was performed using Agilent GC-7890 with an auto sampler.…”
Section: Methodsmentioning
confidence: 99%
“…According to [13] the aqueous crude extracts of tobacco leaves had antifeedant activity against FAW larvae, with the highest concentration (50%) exhibiting the highest mortality. In a study by [14] the ethanolic extracts of the dehydrated leaves of Cedrela odorata and Piper auritum presented insecticidal activity as high (100% mortality at a concentration of 92 mg/cm 2 ) as that obtained with the positive control, Melia azedarach L. (Sapindales: Meliaceae). Furthermore, seed oil and leaf extracts from A. indica and plant oil from turmeric (Curcuma longa L.) have shown to be promising in controlling FAW larvae under laboratory conditions [15] [16].…”
Section: Introductionmentioning
confidence: 96%